Repeatability and Reproducibility of Microdosimetry With a Mini-TEPC - Bianchi, A.; Selva, A.; Colautti, P.; Petringa, G.; Cirrone, P.; Reniers, B.; Parisi, A.; Vanhavere, F.; Conte, V. (Frontiers in Physics, 2021)
Experimental microdosimetry measures the energy deposited in a microscopic sensitive volume by single ionizing particles traversing it or passing by. The fundamental advantage of experimental microdosimetry over the computational approach is that the first allows to determine distributions of energy deposition when information on the energy and nature of the charged particles at the point of interest is incomplete or fragmentary. This is almost always the case in radiation protection applications, but discrepancies between the modelled and the actual scenarios should be considered also in radiation therapy. Models for physical reality are always imperfect and rely both on basic input data and on simplifications that are necessarily implemented. Furthermore, unintended events due to human errors or machine/system failures can be minimized but cannot be completely avoided. Though in proton radiation therapy (PRT) a constant RBE of 1.1 is assumed, there is evidence of an increasing RBE towards the end of the proton range. Treatment Planning Systems (TPS) that consider a variable LET or RBE are already available. However, while the calculated dose distributions are routinely verified with ionization chambers as part of the quality assurance program (QA), there is no commercial detector currently available to perform routine verification of the radiation quality calculated by the TPS through LET or RBE. Verification of calculated LET is required to assure that a robustly optimized plan is delivered as planned. The scientific community agrees that a new domain of QA additionally to the physical dose verification is required, and microdosimetry can be the right approach to address that. Important prerequisites are the repeatability and reproducibility of microdosimetric measurements. This work aims at studying experimentally these characteristics of measurements performed with a miniaturized Tissue Equivalent Proportional Counter (mini-TEPC) in a 62 MeV proton beam. Experiments were carried out within one year, without gas recharging and by different operators. RBE was also calculated by applying the Loncol’s weighting function to microdosimetric distributions. Demonstration of reproducibility of measured microdosimetric quantities yF, yD and RBE10 makes this TEPC a possible tool for LET verification in proton therapy. Future characterization will be performed in higher energy proton beams.